2012
DOI: 10.1021/jp309358h
|View full text |Cite
|
Sign up to set email alerts
|

On the Combustion Chemistry of n-Heptane and n-Butanol Blends

Abstract: High-speed gas sampling experiments to measure the intermediate products formed during fuel decomposition remain challenging yet important experimental objectives. This article presents new speciation data on two important fuel reference compounds, n-heptane and n-butanol, at practical thermodynamic conditions of 700 K and 9 atm, for stoichiometric fuel-to-oxygen ratios and a dilution of 5.64 (molar ratio of inert gases to O(2)), and at two blend ratios, 80%-20% and 50%-50% by mole of n-heptane and n-butanol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 56 publications
(124 reference statements)
1
40
0
Order By: Relevance
“…The reduction in low-temperature ignition propensity (lower cetane numbers) when alcohols are blended with petroleum fuels is caused by the alcohol acting as a sink of reactive species that reduces the overall chain-branching reaction rates and, thus, slows ignition [171,176], as discussed above in the context of the octane ratings. The high-octane tert-butanol has a highly-branched structure that results in it having the lowest reactivity, and hence smallest cetane number, of the butanol isomers, as well as a lower cetane number than ethanol [176].…”
Section: Alcohol-diesel Blends For CI Enginesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in low-temperature ignition propensity (lower cetane numbers) when alcohols are blended with petroleum fuels is caused by the alcohol acting as a sink of reactive species that reduces the overall chain-branching reaction rates and, thus, slows ignition [171,176], as discussed above in the context of the octane ratings. The high-octane tert-butanol has a highly-branched structure that results in it having the lowest reactivity, and hence smallest cetane number, of the butanol isomers, as well as a lower cetane number than ethanol [176].…”
Section: Alcohol-diesel Blends For CI Enginesmentioning
confidence: 99%
“…When blended with hydrocarbon fuels, ethanol acts as a sink of reactive species (OH radicals) that disrupts the chain branching of the hydrocarbon fuel under lowtemperature chemistry conditions and slows ignition of the blend [140,169]. Butanol, similarly, is seen to retard the low-temperature chemistry of n-heptane, a gasoline primary reference fuel and common surrogate fuel-blend component, by fundamentally changing the reaction pathways of the hydrocarbon fuel when it is added to a blend, thereby increasing the octane rating of the fuel blend [171,172]. As the hydrocarbon chain increases from n-butanol to n-hexanol, the reactivity at low temperatures increases, due to more low-temperature chemistry for the longchain alcohols [173].…”
Section: Alcohol Fuel Effects On Si Engine Performance and Emissionsmentioning
confidence: 99%
“…Recent work has focused on primary reference fuels (PRFs), biofuels, and biofuel/PRF blends, including work with n-heptane [92], iso-octane [93], n-butanol [94], n-heptane/n-butanol blends [95], and methyl-butanoate [96]. These studies found that, although most chemical kinetic models are able to predict the ignition delay time fairly well (e.g., within 20% typically), the predictions of some species profiles deviate from those measured experimentally, and this may influence the model's ability to predict combustion features besides ignition delay time, e.g., soot formation and/or emissions.…”
Section: Diagnostics In Rcm Experimentsmentioning
confidence: 99%
“…Similar experiments at atmospheric pressure were conducted by Zhang et al [38], coming to similar conclusions. Using a rapid compression facility, Karwat et al [39] explored the effects of blending n-heptane/n-butanol on ignition delays, finding that butanol slowed ignition relative to pure n-heptane. In addition, Karwat et al [39] found that the presence of n-heptane caused n-butanol to react at temperatures it would otherwise be non-reactive.…”
Section: Introductionmentioning
confidence: 99%